Non-Differentiable Functions Defined in Terms of Classical Representations of Real Numbers - Serbenyuk, S.O. (Журнал математической физики, анализа, геометрии, 2018)
The present paper is devoted to the functions from a certain subclass of non-differentiable functions. The arguments and values of the considered functions are represented by the s-adic representation or the nega-s-adic representation of real numbers. The technique of modeling these functions is the simplest as compared with the well-known techniques of modeling non-differentiable functions. In other words, the values of these functions are obtained from the s-adic or nega-s-adic representation of the argument by a certain change of digits or combinations of digits. Цю роботу присвячено деякому пiдкласу недиференцiйовних функцiй. Аргументи i значення функцiй, що розглядаються, подано через s-ве або нега-s-ве зображення дiйсних чисел. Технiка моделювання таких функцiй є простiшою в порiвняннi з добре вiдомими технiками моделювання недиференцiйовних функцiй. Iншими словами, значення цих функцiй отримано з s-го або нега-s-го зображення аргументу за допомоги певно замiни цифр чи комбiнацiй цифр.